2017
DOI: 10.1038/sj.bdj.2017.1039
|View full text |Cite
|
Sign up to set email alerts
|

MRONJ risk of adjuvant bisphosphonates in early stage breast cancer

Abstract: Medication-related osteonecrosis of the jaw (MRONJ) has most commonly been associated with bisphosphonates. The routine uses of these drugs are now well established predominantly in metastatic cancer with bone involvement, multiple myeloma, hypercalcaemia, osteoporosis and Paget's disease. Recently, however, the use of bisphosphonates in early breast cancer has shown a reduction in breast cancer recurrence and breast cancer deaths. This new indication for their use approximates to a further 20,000 women per ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
0
17
0
2
Order By: Relevance
“…Recent studies have reported the presence of histologically proven alveolar necrotic bone associated with dental/periodontal infection at the time of the extraction of teeth (Nicolatou-Galitis et al, 2015;Nicolatou-Galitis, Schiødt, et al, 2019). Similarly, animal studies have reported that MRONJ can develop to areas of periodontal infection in the absence of dental extraction surgery (Nowicki et al, 2019; (Patel et al, 2018;Rugani et al, 2014). The Group suggested that, in order to optimize risk assessment and management of patients on anti-resorptive therapy, it is important to highlight to all clinicians and, in particular in the dental setting, that the risk of MRONJ development is mostly associated with high cumulative dosage of nitrogencontaining bisphosphonates.…”
Section: Controver S Ie S On Ris K Fac Tor Smentioning
confidence: 98%
See 1 more Smart Citation
“…Recent studies have reported the presence of histologically proven alveolar necrotic bone associated with dental/periodontal infection at the time of the extraction of teeth (Nicolatou-Galitis et al, 2015;Nicolatou-Galitis, Schiødt, et al, 2019). Similarly, animal studies have reported that MRONJ can develop to areas of periodontal infection in the absence of dental extraction surgery (Nowicki et al, 2019; (Patel et al, 2018;Rugani et al, 2014). The Group suggested that, in order to optimize risk assessment and management of patients on anti-resorptive therapy, it is important to highlight to all clinicians and, in particular in the dental setting, that the risk of MRONJ development is mostly associated with high cumulative dosage of nitrogencontaining bisphosphonates.…”
Section: Controver S Ie S On Ris K Fac Tor Smentioning
confidence: 98%
“…For example, some osteoporosis patients receive yearly intravenous bisphosphonates; however, because the cumulative dosage remains low, their risk of developing MRONJ is also low. Furthermore, a low dose, usually quarterly or half‐yearly, of prophylactic intravenous bisphosphonates has been recently introduced in the management of breast cancer patients without metastases (adjuvant therapy), and this has been reported to be associated with notably lower risk of MRONJ development (Patel et al, ; Rugani et al, ). The Group suggested that, in order to optimize risk assessment and management of patients on anti‐resorptive therapy, it is important to highlight to all clinicians and, in particular in the dental setting, that the risk of MRONJ development is mostly associated with high cumulative dosage of nitrogen‐containing bisphosphonates.…”
Section: Controversies On Risk Factorsmentioning
confidence: 99%
“…In vitro studies indicate that leflunomide selectively inhibits RANK-L-induced differentiation of osteoclast, which in turn directly affects bone remodelling as well as inhibiting several tyrosine kinases. 1 These actions are exactly those targeted by the various implicated MRONJ drugs mentioned earlier.…”
Section: Mronj Risk Factormentioning
confidence: 68%
“…In the available literature the drilling of a cavity into a tooth to create an application point during elevation has been described. 1,2 In our case this tooth already had an appropriately sized buccal cavity created by caries subgingivally and hence no drilling was required (Fig. 1).…”
Section: A Helpful Wisdom Toothmentioning
confidence: 76%
“…Prevention forms the main management approach for patients taking anti-resorptive or anti-angiogenic drugs 4. Patients are often unaware of the possible risk until it is discussed before tooth removal or when they present with symptoms.…”
Section: How Can It Be Prevented?mentioning
confidence: 99%